Association of the QRS duration on the resting electrocardiogram with the severity of coronary artery disease in 2,196 patients undergoing coronary angiography for suspected coronary artery disease - Kannam, Hari; Aronow, Wilbert; Chilappa, Karin; Devabhakturi, Srikala; Singh, Tarunjit; Kalapatapu, Kumar; Weiss, Melvin B.; Pucillo, Anthony L.; Monsen, Craig E. (Archives of Medical Science, 2009)
Introduction: To investigate the association between QRS duration on the resting electrocardiogram (ECG) with severity of coronary artery disease (CAD) in patients undergoing coronary angiography for suspected CAD. Material and methods: We investigated the prevalence of a QRS duration ł 120 ms on the resting ECG in patients with no CAD, nonobstructive CAD, 1-vessel obstructive CAD, 2-vessel obstructive CAD, and 3-vessel obstructive CAD undergoing coronary angiography for suspected CAD. The 2,196 patients included 1,291 men and 905 women, mean age 69 ±10 years, with suspected CAD. Nonobstructive CAD was diagnosed if there was 50% obstruction of at least 1 major coronary artery. Results: A QRS duration of ł 120 ms on the resting ECG was present in 30 of 220 patients (14%) with no CAD, in 44 of 276 patients (16%) with nonobstructive CAD, in 76 of 441 patients (17%) with 1-vessel CAD, in 99 of 464 patients (21%) with 2-vessel CAD, and in 217 of 795 patients (27%) with 3-vessel CAD (p < 0.001 comparing 5 with 1, 5 with 2, and 5 with 3; p < 0.02 comparing 5 with 4 and 4 with 1). Conclusions: The prevalence of a QRS duration ł 120 ms on the resting ECG increased with increasing severity of obstructive CAD.